Prevalence of Multidrug-Resistant Escherichia coli Isolated from Drinking Water Sources - Odonkor, S.T.; Addo, K.K. (International Journal of Microbiology, 2018)
The control of infectious diseases is badly endangered by the rise in the number of microorganisms that are resistant to antimicrobial agents. This is because infections caused by resistant microorganisms often fail to respond to conventional treatment, resulting in prolonged illness and greater risk of death. Antimicrobial-resistant bacteria are also present in various water sources. This study therefore sought to document the microbiological quality and antibiograms of bacterial isolates (E. coli strains) from six different water sources in order to determine their safety for human consumption and to provide updated antibiotic data for pragmatic treatment of patients. Bacteria isolation and identification was done using API and conventional methods. Antibiotic susceptibility testing was conducted using the Kirby–Bauer method. Results obtained indicated that all the water sources tested were of poor quality. Bacteria isolated included E. coli, Enterobacter spp., Klebsiella spp., Salmonella typhi, Streptococcus spp., Proteus vulgaris, Vibrio cholera, Shigella spp., Pseudomonas aeruginosa, and Enterococcus faecalis. The prevalence of multidrug-resistant E. coli was 49.48%. E. coli isolates showed high resistance patterns to the tested antibiotics. They were most resistant to penicillin (32.99%), cefuroxime (28.87%), erythromycin (23.71%), and tetracycline (21.45%). In contrast, they were susceptible to nitrofurantoin (93.8%), cefotaxime and amikacin (91.75%), gentamicin (90.7%), nalidixic acid (89.65%), ciprofloxacin (74.2%), chloramphenicol (69.07%), pipemidic acid (65.97%), and cefuroxime (52.58%). Sixty-three percent (63%) of the multidrug-resistant E. coli strains recorded a multiple antibiotic resistance (MAR) index value >0.2. The susceptible antibiotics, especially the nitrofurantoin, are hence recommended in the practical treatment of waterborne bacterial diseases.